The impact of hydrothermal carbonisation on the char reactivity of biomass - Stirling, Robert J.; Snape, Colin E.; Meredith, Will (Elsevier, 2018)
Hydrothermal carbonisation (HTC) is an attractive biomass pre-treatment as it produces a coal-like fuel, can easily process wet biomass and wastes, and lowers the risk of slagging and fouling in pulverised fuel (PF) combustion boilers. One of the major factors in determining the suitability of a fuel as a coal replacement for PF combustion is matching the char reactivity and volatile matter content to that of coals, as these significantly affect heat release and flame stability. The char reactivity of wood and olive cake biocoals and their respective drop tube furnace chars have been studied using thermogravimetric analysis in comparison to other biomass fuels and high-volatile bituminous coal. It was found that HTC reduces the reactivity of biomass, and in the case of HTC of wood pellets the resulting biocoal has a char reactivity similar to that of high-volatile bituminous coal. Proximate analysis, X-ray fluorescence analysis, and textural characterisation were used to show that this effect is caused primarily by removal of catalytic alkali and alkaline earth metals. Subsequent torrefaction of the wood biocoals was performed to tailor their volatile matter content to match that of sub-bituminous and high volatile bituminous coals without major impact on char reactivity.